Double-layer synergistic optimization by functional black phosphorus quantum dots for high-efficiency and stable planar perovskite solar cells. (December 2021) - Zhang, Yuhong; Xu, Lin; Wu, Yanjie; Zhou, Qingqing; Shi, Zhichong; Zhuang, Xinmeng; Liu, Bin; Dong, Biao; Bai, Xue; Xu, Wen; Zhou, Donglei; Song, Hongwei
Abstract: Additive engineering is one of the most effective techniques for optimizing the performance of perovskite solar cells (PSCs). However, the previous research mainly focused on adopting this strategy to a single layer of the PSCs. In this work, a double-layer synergistic optimization approach is employed by simultaneously introducing functional black phosphorus quantum dots (BPQDs) into the electron transport layer (ETL) and perovskite layer. The BPQDs with superior conductivity is doped into SnO2 ETL to effectively fill the electron traps and enhance electron mobility of SnO2 . Meanwhile, the 3-aminopropyltriethoxysilane-modified BPQDs (BPQDs@APTES) is introduced into the perovskite bulk to moderately tailor its intrinsic characteristics, and this synchronously facilitates the perovskite nucleation and growth, passivates defects and improves moisture-resistance of perovskite film. Taking advantage of the synergistic effects, efficient PSCs with power conversion efficiency of 22.85% with ultrahigh open-circuit voltage ( V OC ) of 1.22 V is demonstrated, this V OC value ranks in the highest values of perovskite film with a bandgap of ~ 1.60 eV. Additionally, the non-encapsulated BPQDs modified PSCs show better long time and humidity stability. Graphical Abstract: In this work, a double-layer synergistic optimization strategy is demonstrated through incorporating functional black phosphorus quantum dots (BPQDs) into the SnO2 and perovskite layer. Eventually, the perovskite solar cells (PSCs) with functional BPQDs modification achieve a champion efficiency of 22.85% with ultrahigh open-circuit voltage ( V OC ) (1.22 V). This work provides a route to design strategies within electron transport layer (ETL) and perovskite bulk to improve the performance of the PSCs. ga1 Highlights: The BPQDs is designed as a bifunctional reagent and synchronously incorporated into the SnO2 and perovskite bulk. The BPQDs can effectively fill the electron traps and passivate defect of SnO2 . The BPQDs@APTES can facilitate perovskite growth, passivate defects and improve moisture-resistance of perovskite film. High-efficiency (22.85%) PSCs with a VOC of 1.22 V are reported for a perovskite film having a bandgap of ~ 1.60 eV. The double-layer synergistic optimization strategy provides an avenue for further improve the performance of PSCs.